PENINGKATAN HASIL BELAJAR MENGGUNAKAN TIPE NUMBERED HEADS TOGETHER PADA PEMBELAJARAN IPS KELAS IV SD - Islimanara, Harfa; Marli, Suhardi; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to describe the civics learningÂ outcomes by using numbered heads together in the fourth grade public elementary school 56 West Pontianak. The method that used in this research was descriptive method with a form of classroom action research. The subject in this research were teacher and 30 students of class IV. The procedure in this research consists of four step: planning, action, observation, and reflection. The data collection technique that used in this research were direct observation technique and scrutiny documents. The data collection technique that used in this research were observation sheets and sheets of scrutiny documents. This research result: 1) the ability of teacher to plan learning in cycle 1, with an average score of 3,45. In cycle 2 and cycle 3 becomes 3,77 to 3,85. 2) the ability of teacher in implementing the learning in the first cycle, with an average score of 3,57, in cycle 2 to 3,72, in cycle 3 to 3,75. 3) An increase in the average learning outcomes of class IV at first cycle is 79,67 the second cycle increase to 87,67 and in cycle 3 into 89,67.Â Keywords: Learning Outcomes, Civics Learning, NHT